The forensic context in Nursing’s everyday practice (Research, Society and Development, 2020)
Objectives: to identify nurses' knowledge of forensic sciences, describe how forensic sciences could be applied in nursing and discuss the insertion of forensic science for nursing care. Method: Descriptive study with a qualitative approach, including five nurses and five nursing residents of pediatric and medical clinic wards of a university hospital in the city of Rio de Janeiro. As a data collection instrument, semi-structured interviews were used and for data analysis, the content analysis technique. Results: evidenced the absence of the concept of forensic sciences in nurse’s daily life, however, nurses work every day in cases of violence, identifying the signs and collecting traces. Conclusion: nurses play an important role in cases of violence, however, the lack of knowledge and specialization can often keep these professionals away from monitoring and resolving those cases.